Studi Perbandingan Kuat Tekan Paving Block Berbahan Dasar Limbah Plastik - Mustakim, Mustakim; Rahima, Rahima; Muis, Abd; Sulfanita, Andi (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2023)
The waste problem in Indonesia is an unfinished problem. The growing population increases the amount of waste originating from human activities, both organic and inorganic waste. Inorganic waste such as plastic waste is difficult to decompose naturally, so research is needed on the use of plastic waste to make environmentally friendly paving blocks. The aim of this research is to know the compressive strength and the percentage of water absorption value. Using experimental data collection techniques or methods (testing/observation). By testing intact paving blocks and cubes, the results showed that PET plastic types did not meet the testing standards for DHPE and PP plastic types, which had varying compressive strength and water absorption, so that research could be continued. The highest compressive strength of the PP plastic type was 16.98 Mpa for the intact model and 23.30 Mpa for the cube model, the lowest water absorption capacity was obtained for the PP plastic type of 0.38%.